2021
DOI: 10.2174/1573405617999210112193545
|View full text |Cite
|
Sign up to set email alerts
|

Could Computed Tomography Hounsfield Unit Values of Lumbar Vertebrae Detect Osteoporosis?

Abstract: Background: Dual-energy X-ray absorptiometry (DEXA) scanning has several disadvantages determining osteoporosis especially for the degenerative spine. Introduction: To determine spinal osteoporosis in patients suffering from lumbar degenerative disease using computed tomography (CT). Methods: A total of 547 subjects that underwent DEXA and abdominal CT within a period of three months were examined retrospectively and separated into groups based on lumbar degenerative alteration on the CT scan. The subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…12 Another study, which included 340 patients with normal BMD on DEXA scan and evidence of DLD on CT scan, demonstrated that 44.2% of patients had OP as determined by CT HU calculations. 10 Similarly, our study demonstrates that of our 74 patients who had non-OP bone determined by DEXA, 46% of these patients had OP as defined by CT-derived HU calculations. The present data support published evidence but suggests that the prevalence of undiagnosed OP in the spine is higher than previously described.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…12 Another study, which included 340 patients with normal BMD on DEXA scan and evidence of DLD on CT scan, demonstrated that 44.2% of patients had OP as determined by CT HU calculations. 10 Similarly, our study demonstrates that of our 74 patients who had non-OP bone determined by DEXA, 46% of these patients had OP as defined by CT-derived HU calculations. The present data support published evidence but suggests that the prevalence of undiagnosed OP in the spine is higher than previously described.…”
Section: Discussionsupporting
confidence: 64%
“…The same group later demonstrated that DEXA T -scores are unreliable in patients with DLD 12 . Another study, which included 340 patients with normal BMD on DEXA scan and evidence of DLD on CT scan, demonstrated that 44.2% of patients had OP as determined by CT HU calculations 10 . Similarly, our study demonstrates that of our 74 patients who had non-OP bone determined by DEXA, 46% of these patients had OP as defined by CT-derived HU calculations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, our results showed forearm and femoral neck T-scores were more significantly correlated with arm and calf circumference and volume than lumbar T-scores. This is likely explained by the well documented limitation of DEXA scans in degenerative spine, especially given the age of our patient population[ 24 ]. The overall low DEXA T-score values of our sample are likely due to nature of the patient population of patients being evaluated at the bone health clinic.…”
Section: Discussionmentioning
confidence: 99%
“…CT HU values strongly correlate with DXA BMD values and different CT HU thresholds for the diagnosis of osteoporosis in the lumbar spine have been proposed. [7][8][9][10][11][12][13][14][15][16] The measurement of CT HU values is reliable, with excellent intra-and interobserver reliability. 9 HU measurements correlate with future osteoporotic fracture risk, 17 adjacent segment fractures after spinal fusion, 18 cage subsidence after transforaminal lumbar interbody fusion (TLIF), 19 pedicle screw loosening, [20][21][22] symptomatic pseudarthrosis after posterolateral 23 and proximal junctional failure after posterior lumbar fusion.…”
Section: Introductionmentioning
confidence: 99%